1999
DOI: 10.1128/jvi.73.6.4847-4855.1999
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ RNA Terminus of Spleen Necrosis Virus Contains a Novel Posttranscriptional Control Element That Facilitates Human Immunodeficiency Virus Rev/RRE-Independent Gag Production

Abstract: Previous work has shown that spleen necrosis virus (SNV) long terminal repeats (LTRs) are associated with Rex/Rex-responsive element-independent expression of bovine leukemia virus RNA and supports the hypothesis that SNV RNA contains a cis-acting element that interacts with cellular Rex-like proteins. To test this hypothesis, the human immunodeficiency virus type 1 (HIV) Rev/RRE-dependent gag gene was used as a reporter to analyze various SNV sequences. Gag enzyme-linked immunosorbent assay and Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…In these viruses, the region of genomic RNA between the 5′-LTR and the R-U5 domain was shown to enhance the translation of SNV genomic RNA and was subsequently termed the post-transcriptional control element (PCE). Interestingly, this effect was also demonstrated when this PCE was inserted upstream of both the main reading frame of the HIV-1 RNA and a Luciferase reporter gene [65][66][67] . Quantitative RNA analysis, together with ribosomal sedimentation profile analysis, has established that this translation enhancement is due to increased ribosome loading of the mRNA.…”
Section: R-u5 Domainmentioning
confidence: 87%
“…In these viruses, the region of genomic RNA between the 5′-LTR and the R-U5 domain was shown to enhance the translation of SNV genomic RNA and was subsequently termed the post-transcriptional control element (PCE). Interestingly, this effect was also demonstrated when this PCE was inserted upstream of both the main reading frame of the HIV-1 RNA and a Luciferase reporter gene [65][66][67] . Quantitative RNA analysis, together with ribosomal sedimentation profile analysis, has established that this translation enhancement is due to increased ribosome loading of the mRNA.…”
Section: R-u5 Domainmentioning
confidence: 87%
“…62,70 However downregulation experiments with siRNAs and quantitative RNA analysis determined RHA is not required for retrovirus transcription, RNA splicing or nuclear export, but that RHA is necessary for retrovirus translation. 57,[71][72][73] RHA selectively interacts with structural features of the 5' UTR of many retroviruses and overexpression of RHA increases their translation. 57,[71][72][73] RHA interaction with the 5' UTR increases polysome association and requires the ATP-binding activity of the DEIH helicase domain.…”
Section: Host-encoded Rna Helicasesmentioning
confidence: 99%
“…57,[71][72][73] RHA selectively interacts with structural features of the 5' UTR of many retroviruses and overexpression of RHA increases their translation. 57,[71][72][73] RHA interaction with the 5' UTR increases polysome association and requires the ATP-binding activity of the DEIH helicase domain. 57,73 The molecular basis of RHA translation activity is catalytic rearrangement of the RNP to facilitate ribosome scanning and translation initiation, and possibly and protein-protein interaction that secures a circular polysome for efficient translation reinitiation.…”
Section: Host-encoded Rna Helicasesmentioning
confidence: 99%
“…Butsch et al have shown that the R/U5 region at the 5' RNA terminus of SNV contains a unique cis-acting posttranscriptional control element that interacts with hypothetical cellular Rev-like proteins and contains stimulatory sequences that function in a 5'-proximal position to enhance initiation of translation of a non-retroviral reporter gene RNA. This facilitates Rev/RRE independent transport and efficient translation of HIV-1 RNA (122,123).…”
Section: Regulatory Modifications Of the Packaging Constructmentioning
confidence: 99%